Clinical trends of intraocular inflammation in tertiary health centre - Sujata Lakhtakiya; Eva Tirkey; Renuka Rawat; Baldev Sastya (International Journal of Health and Clinical Research, 2022)
Aim: To study the clinical pattern of uveitis and its systemic associations in a tertiary care health centre. Methods: This cross sectional, observational study was done on 250 patients with intraocular inflammation presenting to the ophthalmology department from May 2019 to May 2020.Data regarding demographic profile, anatomical location, clinical features and etiology of the disease was collected and analyzed. Thorough systemic and local examination was done and tailored laboratory investigations were advised to find systemic associations of uveitis. Results: Two hundred fifty patients with the intraocular inflammation were examined. The mean age of presentation was 38.3±17.7 years, with most patients belonging to the age group of 20-40 years. The male to female ratio was 1:1.2. Most patients (87.6%) had unilateral disease with acute onset presentation in 81.6%. Anterior uveitis was most common (79.6%) anatomical type and non-granulomatous was most common (93.2%) pathological type. Disease was idiopathic in most (60.4%) cases. Infectious etiology was found in 8.8% cases and non-infectious in 30.8% cases. Most common identifiable causes weretrauma (21.7%) in anterior uveitis, tuberculosis (18.18%) in posterior uveitis, and Vogt Koyanagi Harada syndrome (36.36%) in panuveitis. Conclusion: The pattern of uveitis shows great variation depending upon geographical and environmental factors. This study concluded that uveitis predominantly occurred in young adults with acute presentation being the most frequent. The most common anatomical type was anterior uveitis and pathological type was non – granulomatous. Aspecific aetiology could be identified in only 39.6% cases.